Anxious dwellers: housing, labor and the potentiality of tanks in Nahda - Sabah, Marwa (AUC Knowledge Fountain, 2016)
The neoliberal reconfiguration of the Egyptian metropolis of Cairo has rendered the lives of the working poor in informal and destitute urban neighborhoods precarious. Over the past thirty years many of these families and communities have been resettled to new neighborhoods in desert peripheries of the city. This thesis focuses on the everyday lives of women and their networks that have been relocated to Nahda, arguably one of the most targeted neighborhoods in Cairo for relocated and displaced communities. Resettlement is a costly process especially for the working poor who not only have to deal with the physical and emotional costs of relocation, but also equally struggle to secure their livelihoods in light of a continual threat of dispossession and displacement. This constant threat for the poor is part and parcel of the neoliberal city, which is premised on the relentless drive to generate space for new capital. Movement is an essential part of the everyday lives of the two generations of women in Nahda among whom I conducted fieldwork. In this thesis I explore how relocation to, and the perpetual mobility of populations in and out of Nahda, have shaped the ways in which my interlocutors reconstruct their social spaces, spaces in which news meanings of friendship, trust, security, home, and family are created and are constantly changing. Through their everyday strategies of emplacement, I look at how my interlocutors created new networks, which not only enable them to secure their livelihoods, but have also replaced their severed ties from their "original" neighborhoods. I examine how my interlocutors take risks with whatever possible means attainable to them, be it marriage, selling vegetables or having a child , to survive in an informal economic structure. I explore how in their struggle for and to secure housing they both use the law to claim rights from the state and gain visibility, and subvert that same law to navigate the threat of relocation. Finally, I explore not only the effects of the January 25, 2011 popular uprising on the neighborhood, but of equal significance the relationships between precarity and “the event" (January 25, 2011 uprising) and the dreams of my interlocutors in envisioning better and other futures.